Use of CAD-based pre-bent implants reduces theatre time in orbital floor reconstruction: results of a prospective study. Issue 7 (September 2020) - von Wilmowsky, C.; Schwertner, M.G.; Nkenke, E.; Moest, T.; Adler, W.; Ebker, T.
Abstract: In this prospective study we evaluated the duration of insertion and the accuracy of fitting of computer-aided design (CAD)-based pre-bent orbital floor plates compared with non-preformed orbital plates in reconstruction of the orbital floor. Thirty-six patients with unilateral fractures of the orbital floor were included; pre-bent plates were used in 25 and non-preformed plates in 11. Preoperative computed tomography (CT) scans were used for CAD of individualised implants. The anatomy of the affected orbit was virtually reconstructed "slice by slice". Individually pre-bent plates were generated using a stereolithographic model of the reconstructed orbit. The mean (SD) duration of insertion was significantly reduced when pre-bent orbital plates were used (5.5 (5.4) min) compared with non-preformed meshes (11.1 (7.7) min). The congruence of pre-bent plates to the infraorbital rim did not differ from that of non-preformed plates. The accuracy of fit was rated as "accurate" in 24 cases. CAD-based individualised titanium meshes reduce theatre time compared with non-preformed orbital plates. Our results confirm the efficacy of CAD-based pre-bent plates in reconstruction of the orbital floor.